DIVERSITY OF BATS IN HILL FORESTS OF ITAYA RIVER, LORETO, PERU - RAMOS RODRÍGUEZ, María Claudia (2017)
Bats are one of the most diverse groups of mammals in Peru, and they are also the most feared by the human population, which mostly ignores the qualities and ecological potential governed by their feeding strategies. Therefore, we had the objective of knowing the diversity of these flying mammals in the hill forests of the upper Itaya river basin, in the department of Loreto, Peru. Between 2009 and 2011, we took captures at the understory and middle canopy level in 50 sampling units. The result of the effort of 1800 hours/net 0 registered a species richness ( D) of 47 species, equivalent to 79.6% of the total estimated for this part of the 0 Peruvian Amazon. The D shows significant differences at the stratum level (t = 3.28, p = 0.01), with a greater number of understory species than the middle canopy. In addition, species richness was increased with 17 new records for the area. The frugivorous species Rhinophylla pumilio, Artibeus obscurus and Carollia brevicauda were dominant (λ = 0.94). Likewise, the proportional comparisons made in terms of size, age and food guild, showed significant differences, even when they remained homogeneous at the level of strata 1 (<0.0001). The true diversity ( D) shows an effectiveness of 24.51 species for the hill forests, remaining similar in both strata (t = 0.94, p = 0.24). The diversity of bats recorded in this study could be influenced by the increase in extractive activities during the last decade. We consider it opportune to take measures of political influence to manage in a sustainable way the use of the resources used in this part of the Peruvian Amazon.